Stabilitas Kimia Nanoemulsi Gel Kombinasi Eugenol dan Sitronellal: Chemical Stability of Gel Nano Emulsion Combination of Eugenol and Sitronellal - Fitria, Wahda; Saputri, Fadlina Chany; Jufri, Mahdi (Jurnal Sains dan Kesehatan, 2024)
Clove oil and lemongrass essential oil can be formulated into Nanoemulsion Gel preparations as topical preparations for the skin. This Nanoemulsion Gel preparation is formulated by first making a nanoemulsion preparation, which is then made into a Nanoemulsion Gel preparation by dispersing the nanoemulsion into a gel that has been made with active ingredients from clove oil and lemongrass essential oil. The gel nanoemulsion preparation was then analyzed for the stability of its chemical components using GC-MS. The results of analysis using GC-MS obtained that a Nanoemulsion Gel preparation formulated from clove oil and lemongrass oil was chemically stable.   Keywords:          Nanoemulsion gel preparation, Chemical stability, GC-MS   Abstrak Minyak atsiri cengkeh dan minyak atsiri sereh dapat diformulasikan menjadi sediaan nanoemulsi gel sebagai sediaan topikal pada kulit. Sediaan nanoemulsi gel ini diformulasikan dengan terlebih dahulu membuat sediaan nanoemulsi, yang selanjutnya dibuat menjadi sediaan nanoemulsi gel dengan mendispersikan nanoemulsi ke dalam gel yang telah dibuat dengan bahan aktif dari minyak atsiri cengkeh dan minyak atsiri sereh. Sediaan nanoemulsi gel kemudian dianalisis stabilitas komponen kimianya dengan menggunakan GC-MS. Hasil analisis menggunakan GC-MS diperoleh sediaan nanoemulsi gel yang diformulasikan dari minyak cengkeh dan minyak sereh cukup stabil secara kimia.   Kata Kunci:         sediaan Nanoemulsi Gel, stabilitas Kimia, GC-MS